Detection and clinical relevance of hematogenous tumor cell dissemination in patients with ductal carcinoma in situ - Banys-Paluchowski, Maggie; Hahn, Markus; Gruber, Ines; Krawczyk, Natalia; Wallwiener, Markus; Hartkopf, Andreas; Ţăran, Florin-Andrei; Röhm, Carmen; Kurth, Ralf; Becker, Sven; Solomayer, Erich-Franz; Wallwiener, Diethelm; et al. (Breast cancer research and treatment, 2014)
Hematogenous tumor cell dissemination is a crucial step in systemic disease progression and predicts reduced clinical outcome in breast cancer patients. Only invasive cancers are assumed to shed tumor cells into the bloodstream and infiltrate lymph nodes. However, recent studies revealed that disseminated tumor cells (DTCs) may be detected in bone marrow (BM) of patients with preinvasive lesions, i.e., ductal carcinoma in situ (DCIS). The purpose of this analysis was to examine the incidence and clinical value of DTC detection in a large series of patients with pure DCIS. 404 patients treated for DCIS at the University Hospital Tuebingen, Germany were included into this analysis.
Gesehen am 21.08.2020